Tomorrow’s School’s Review - Leon Benade; Nesta Devine (New Zealand Journal of Teachers' Work)
Wide-ranging changes proposed by the Tomorrow’s Schools Independent Taskforce (2018) seek to end the 30-year period known as ‘Tomorrow’s Schools’, or, what we earlier referred to as the ‘Thirty Years War’ (Devine, Stewart & Benade, 2018).Tomorrow’s Schools (New Zealand Taskforce to Review Education Administration, 1988) emerged from the reform period of the mid-1980s, propelling New Zealand to the forefront of neoliberal policy-making. The current taskforce, composed of notable educationists, has endeavoured to arrive at proposals that emphasise educational interests rather than the competitive commercial interests promoted by Treasury in 1988.